A Mixed-Methods Study Exploring Coping Self-Insights Associated with Resilience - Kirsten J. Bucknell; Scott Hoare; Maria Kangas; Eyal Karin; Monique F. Crane (Behavioral Sciences)
Self-insight has been associated with psychological resilience; however, less is understood about the role coping-specific self-insights play in strengthening resilience. This study used a convergent mixed-methods approach to investigate the coping self-insights triggered by self-reflection on coping experiences and their effects on perceived resilience. Australian ministry workers (n = 79) provided up to five qualitative self-reflective workbook entries, and quantitative online self-report survey responses before and six months after training. Hierarchical regression analyses of weighted quantized coping-specific self-insights on perceived resilience were conducted. Results suggest two pathways for the strengthening of resilience. A set of three self-insights related to greater perceived resilience appear to reinforce and sustain resilient beliefs across six months to increase perceived resilience. Another set of four self-insights is related to lesser perceived resilience after six months. It is suggested that the first set of self-insights may enhance beliefs that support resilience in the mid-term, whereas the second set may promote self-awareness that reduces perceived resilience in the mid-term. These findings support further exploration of coping self-insights, and the use and on-going testing of self-reflection resilience training.